OPEN INNOVATION IN AUTOMOTIVE SMEs SUPPLIERS: AN OPPORTUNITY FOR NEW PRODUCT DEVELOPMENT (Revista Galega de Economía)
The main goal of this study is to determine which open innovation practices can be especially useful to SMEs in the automobile sector in the development of new products and services. We aim to encourage practitioners to study and implement open innovation practices as a way of satisfying the changing needs of the market and remaining competitive. In order to do this, we describe in detail one specific open innovation practice that we consider to be a useful tool for systematizing new product development processes: joint development.